Enterprise optimization for solving an assignment and trim-loss non-convex problem - Rodriguez, Maria Analia (2008)
In the present work, the planning and cutting problem for the corrugated board boxes industries is presented. This problem belongs to the category of the trim-loss problem, which is essential in the paper-converting supply chain management. Bilinear terms in demand and stock constraints, for instance, lead to a non-convex formulation. Two global convex models are formulated and tested. Results obtained in the problem solution are shown. The most efficient model is implemented by means of Java programs and GAMS, a mathematical optimization program. The system is linked to the company ERP (enterprise resource planning) system. Several issues are optimized and improved: waste generation, energy demand, environmental impact and production costs. Paper reel stock management is improved due to more accurate and statistical information obtained by the system. The planning system linked to the ERP connection allows the integration of customers and suppliers increasing the company competitiveness.